Rancang Bangun Vending Machine Komponen Elektronika dengan Identifikasi RFID Berbasis IoT - Soleh, M. Zikri; Salamah, Irma; Rakhman, Abdul (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Electronic components are objects that are supporting parts of an electronic circuit that can operate according to their application. Among them are PCB boards, resistors, transistors, and many more. In assembling a series of students, additional components are often needed which are caused by errors in assembling a circuit. An error in assembling causes a component to be damaged, because the electronic component given by the lecturer is only once. Based on the explanation above, a solution can be found in the form of the application of vending machines for electronic components that can be applied in certain places, such as in the Telecommunication Engineering lab of the Indonesian National Police.  Vending machine is a machine that can accommodate certain objects and can eject them automatically with a trigger programed by the designer, in this case electronic components are used as objects that will be removed from the box. With this tool aims to make it easier for students to get electronic components for free practically and not spend a lot of time, they can use Radio Frequency Identification (RFID) as a detection tool on the vending machine. This research uses RFID technology where, when the user wants to take one of the components of the vending machine, the user must have an RFID-based card that has been previously made so that it can proceed to the next stage, namely component retrieval.